Identification of NTRK gene fusions in lung adenocarcinomas in the Chinese population - Ruiying Zhao; Feng Yao; Chan Xiang; Jikai Zhao; Zhanxian Shang; Lianying Guo; Wenjie Ding; Shengji Ma; Anbo Yu; Jinchen Shao; Lei Zhu; Yuchen Han (Wiley, 2021)
Abstract The molecular profile of neurotrophic tyrosine kinase receptor (NTRK) gene fusions in lung adenocarcinoma (LUAD) is not fully understood. Next‐generation sequencing (NGS) and pan‐tyrosine kinase receptor (TRK) immunohistochemistry (IHC) are powerful tools for NTRK fusion detection. In this study, a total of 4,619 LUAD formalin‐fixed, paraffin‐embedded tissues were collected from patients who underwent biopsy or resection at the Shanghai Chest Hospital during 2017-2019. All specimens were screened for NTRK1 rearrangements using DNA‐based NGS. Thereafter, the cases with NTRK1 rearrangements and cases negative for common driver mutations were analyzed for NTRK1/2/3 fusions using total nucleic acid (TNA)‐based NGS and pan‐TRK IHC. Overall, four NTRK1/2 fusion events were identified, representing 0.087% of the original sample set. At the DNA level, seven NTRK1 rearrangements were identified, while only two TPM3‐NTRK1 fusions were confirmed on TNA‐based NGS as functional. In addition, two NTRK2 fusions (SQSTM1‐NTRK2 and KIF5B‐NTRK2) were identified by TNA‐based NGS in 350 'pan‐negative' cases. Two patients harboring NTRK1/2 fusions were diagnosed with invasive adenocarcinoma, while the other two were diagnosed with adenocarcinoma in situ and minimally invasive adenocarcinoma. All four samples with NTRK fusions were positive for the expression of pan‐TRK. The two samples with NTRK2 fusions showed cytoplasmic staining alone, while the other two samples with NTRK1 fusions exhibited both cytoplasmic and membranous staining. In summary, functional NTRK fusions are found in early‐stage LUAD; however, they are extremely rare. According to this study's results, they are independent oncogenic drivers, mutually exclusive with other driver mutations. We demonstrated that NTRK rearrangement analysis using a DNA‐based approach should be verified with an RNA‐based assay.